2009
DOI: 10.4161/oxim.2.4.9000
|View full text |Cite
|
Sign up to set email alerts
|

Methanol Extract of Ocimum Gratissimum Protects Murine Peritoneal Macrophages from Nicotine Toxicity By Decreasing Free Radical Generation, Lipid and Protein Damage and Enhances Antioxidant Protection

Abstract: In the present study, methanol extract of Ocimum gratissimum Linn (ME-Og) was tested against nicotine-induced murine peritoneal macrophage in vitro. Phytochemical analysis of ME-Og shown high amount of flavonoid and phenolic compound present in it. The cytotoxic effect of ME-Og was studied in murine peritoneal macrophages at different concentrations (0.1 to 100 µg/ml) using the 3-(4, 5-dimethylthiazol-2-yl)-2, 5 diphenyltetrazolium bromide (MTT) method. To establish the protective role of ME-Og against nicotin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
48
0
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 52 publications
1
48
0
7
Order By: Relevance
“…In this experiment, pretreatment with MEOg prevented the depletion of GSH, which was significantly decreased by carrageenan injection in the air pouch. This effect has also been noted by Mahaptara et al [44], who showed that methanol extract of O. gratissimum increases glutathione in nicotine-induced peritoneal macrophages.…”
Section: Discussionsupporting
confidence: 80%
“…In this experiment, pretreatment with MEOg prevented the depletion of GSH, which was significantly decreased by carrageenan injection in the air pouch. This effect has also been noted by Mahaptara et al [44], who showed that methanol extract of O. gratissimum increases glutathione in nicotine-induced peritoneal macrophages.…”
Section: Discussionsupporting
confidence: 80%
“…However, limited scientific evidence regarding the effectiveness of these natural derivatives, and lack of mechanistic understanding has prevented their incorporation into mainstream medicine and their application in human therapy. Eugenol, an important bioactive compound, isolated from O. gratissimum, has a number of beneficial roles [17][18][19][20][21][22][23][41][42][43]. We initially observed its cytotoxic profile in murine peritoneal macrophages by MTT assay, and determined its least comparative cytotoxic concentration to be 15 μg/ml, whereas concentrations higher than 15 μg/ml showed significantly increased cytotoxicity (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…In our previous lab report, it was clearly established that eugenol, and methanol extract of O. gratissimum can decrease the nicotine induced free radical generation, lipid-protein damage, and enhances antioxidant protection in murine peritoneal macrophages [17,18]. Eugenol is used in common medical practice like dentistry for sedation of toothache, pulpitis, and dental hyperalgesia.…”
Section: Introductionmentioning
confidence: 98%
“…It has been shown that nicotine enhanced lipid peroxidation and the production of reactive oxygen species [5]. A fairly recent study reported that nicotine enhanced the activity of NADPH oxidase as well as myeloperoxidase activity in murine peritoneal macrophages [6]. Other studies reported malfunction of antioxidant defense systems through the reduction of the activity of catalase and superoxide dismutase [7].…”
Section: Introductionmentioning
confidence: 99%